Nusinersen in type 1 spinal muscular atrophy: Twelve‐month real‐world data. Issue 3 (8th July 2019) - Pane, Marika; Coratti, Giorgia; Sansone, Valeria A.; Messina, Sonia; Bruno, Claudio; Catteruccia, Michela; Sframeli, Maria; Albamonte, Emilio; Pedemonte, Marina; D'Amico, Adele; Bravetti, Chiara; Berti, Beatrice; et al.
Abstract : Objective: The aim of the study was to report 12‐month changes after treatment with nusinersen in a cohort of 85 type I spinal muscular atrophy patients of ages ranging from 2 months to 15 years and 11 months. Methods: All patients were assessed using the Children's Hospital of Philadelphia Infant Test of Neuromuscular Disorders (CHOP INTEND) and the Hammersmith Infant Neurological Examination‐Section 2 (HINE‐2). Results: Two of the 85 patients had 1 SMN2 copy, 61 had 2 copies, and 18 had 3 copies. In 4 patients the SMN2 copy number was not available. At baseline, the mean CHOP INTEND scores ranged between 0 and 52 (mean = 15.66, standard deviation [SD] = ±13.48), and the mean HINE‐2 score was between 0 and 5 (mean = 0.69, SD = ±1.23). There was a difference between baseline and the 12‐month scores on both the CHOP INTEND and the HINE‐2 for the whole group ( p < 0.001), the subgroups with 2 SMN2 copies ( p < 0.001), and those with 3 SMN2 copies ( p < 0.001). The difference was found not only in patients younger than 210 days at baseline ( p < 0.001) but also in those younger than 5 years on the CHOP INTEND and younger than 2 years on the HINE‐2. Interpretation: Our results, expanding the age range and the severity of type I patients treated with nusinersen over 1 year, provide additional data on the range of efficacy of the drug that will be helpful in making an informed decision on whether to start treatment in patients of different ages and severity. ANN NEUROL 2019;86:443–451